Gambaran Tingkat Ketergantungan Activity Daily Living Pada Pasien Stroke Haemoragik dan Non Haemoragik Berdasarkan Indeks Barthel - N, Raeni; Effendy, Christantie; Haryani, Haryani (School of Nursing Faculty of Medicine Universitas Gadjah Mada, 2008)
Please refer to the file